Etos nauki: Max Weber i Heather E. Douglas o procesualnej odpowiedzialności nauki - Lidia Godek-Ostrouch (Studia Philosophica Wratislaviensia)
In this paper, I reconstruct and compare the concept of the responsibility of science as articulated by Max Weber and Heather E. Douglas. The central issue of this work is the question: In light of Weber’s and Douglas’s considerations, can the social responsibility of science be understood as a process? Answering affirmatively, I reconstruct the concept of responsibility presented by both authors, examining it through the lens of the category of process. This approach allows for the formulation of a new justification for the thesis that science must take into account its social responsibility. One of the hypotheses of the paper posits that, despite the commonly recognized differences in Weber’s and Douglas’s positions regarding the presence of non-epistemic values in science, their arguments and ideas concerning responsibility share several common points.